Analyzing the effect of wall roughness on gas–particle flow in confined channels based on a virtual-wall-group concept. (December 2015) - Cheng, Zhongfu; Zhu, Miaoyong
Highlights: A virtual-wall-group concept for wall roughness was proposed. Rough angle distribution is described by a PDF of multiple collisions. Particle multiple rebounds can be refined into two types. Effects of wall roughness will decline with increasing impact angle. Abstract: Present work aims to develop a particle history effect model for describing the effect of wall roughness on particle–wall collision in confined flow channels. To solve the real distribution function of roughness angle, the effective distribution function is scrutinized with a virtual testing method, and a further virtual-wall-group concept is proposed to investigate the effect of particle motion experience. It is found that roughness angle distribution should be described by a particle history effect–probability distribution function. Rebound angle is rebuilt according to the coordinate rotation operation. Multiple collisions are divided into two types, namely Type I induced by negative rebound and Type II led by positive rebound. Besides, a new probability function is derived to distinguish multiple collisions from a single collision. A set of modified algorithm for multi-collision is built and applied to simulate the particle–rough wall collision, and the predictions are evaluated by the measurements. It reveals that a typical peak can be seen in the probability distributions of both types of multiple collisions, and the effect of wall roughness decreases with the increase of impact angle. The simulated results of confined planar gas–particle flow are good in accordance with the measured data.